CHARACTER AND MORAL VALUE IN “MIRACLE WORKER” BY WILLIAM - Dian Hermayani; Supeno Supeno (INFERENCE: Journal of English Language Teaching, 2020)
This research aims to analyze the characters and moral values contained in the film "Miracle Worker" by William Gibson. Based on the theories of character and moral values collected, four main points are analyzed, they are: 1) How is the character appear in "Miracle Worker" by William Gibson based on the theory put forward by Russel How is moral values that appear in "Miracle Worker" by William Gibson based on the theory put forward by Milhorn. 3) There are three kinds of characters that appear in the characters in "Miracle Worker" by William Gibson based on Russel’s theory, those are the Protagonist, the protagonist played by Kate Keller, Annie Sullivan, Captain Arthur Keller, Mr. Anagnos, and Viney, the Foil, played by Hellen Keller, James Keller, and Aunt Ev, 4) There are six types of moral values that appear in “Miracle Worker" by William Gibson based on Milhorn’s theory, they are: belief, fairness, kind-hearted honesty, responsibility, and tolerance, belief is the most dominant moral values of all moral values that arise.Keywords: character; moral value; moral value; film.